Principal Decision Making in Planning Policies at SD IT Dhinukum Dzoltan - Anggi Anggraini, Aji Pramudya, Dina Oktapia, T. Darmansah, Soleh Parlindungan, Zuchairunnisa (Pusdikra-Publishing.com, 2023)
This research aims to determine the principal's decision making in planning policies at Dhinukum Dzoltan Elementary School. This research method uses a qualitative, phenomenological and descriptive approach. In planning policies in a school, a school principal carries out his duties and functions in three stages, namely implementation, supervision and evaluation. Policy planning is a series of processes for preparing decisions regarding what is expected to happen, such as events, circumstances, atmosphere, and so on. The education policy analysis process is carried out comprehensively, including policy formulation, implementation and impact, with a focus on policy implementation. Therefore, in planning policies in schools, it is important to consider the stages of decision making, as well as supporting and inhibiting factors in policy implementation.